![image](https://tex.z-dn.net/?f=%5Cfrac%7B15a%28a%20-%20b%29%7D%7B40b%28a%20-%20b%29%7D%20%3D%20%20%5Cfrac%7B3a%7D%7B8b%7D%20%20%20%5C%5C%20%20%20%5Cfrac%7By%20%7B%7D%5E%7B2%7D%20%20%20%2B%20y%7D%7B%20%7By%7D%5E%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7By%28y%20%2B%201%29%7D%7B%20%7By%7D%5E%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7By%20%2B%201%7D%7By%7D%20%3C%2Fp%3E%3Cp%3E%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B12x%20-%207%7D%7B15x%7D%20%20%2B%20%20%5Cfrac%7B3x%20%20-%202%7D%7B15x%7D%20%20%3D%20%20%5Cfrac%7B12x%20-%207%20%2B%203x%20-%202%7D%7B15x%7D%20%20%3D%20%20%5Cfrac%7B15x%20-%209%7D%7B15x%7D%20%20%3D%20%20%5Cfrac%7B3%285x%20-%203%29%7D%7B15x%7D%20%20%3D%20%20%5Cfrac%7B5x%20-%203%7D%7B5x%7D%20%20%5C%5C%20%20%5Cfrac%7Bax%20%2B%20ay%7D%7Bx%20%7By%7D%5E%7B2%7D%20%7D%20%20%5Ctimes%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7Dy%20%7D%7B3x%20%2B%203y%7D%20%20%3D%20%20%5Cfrac%7Ba%28x%20%2B%20y%29%20%5Ctimes%20x%20%7B%7D%5E%7B2%7D%20y%7D%7Bx%20%7By%7D%5E%7B2%7D%20%20%5Ctimes%203%28x%20%2B%20y%29%7D%20%20%3D%20%20%5Cfrac%7Bax%7D%7B3y%7D%20%20)
\\ \\ \frac{12x - 7}{15x} + \frac{3x - 2}{15x} = \frac{12x - 7 + 3x - 2}{15x} = \frac{15x - 9}{15x} = \frac{3(5x - 3)}{15x} = \frac{5x - 3}{5x} \\ \frac{ax + ay}{x {y}^{2} } \times \frac{ {x}^{2}y }{3x + 3y} = \frac{a(x + y) \times x {}^{2} y}{x {y}^{2} \times 3(x + y)} = \frac{ax}{3y} " alt="\frac{15a(a - b)}{40b(a - b)} = \frac{3a}{8b} \\ \frac{y {}^{2} + y}{ {y}^{2} } = \frac{y(y + 1)}{ {y}^{2} } = \frac{y + 1}{y}
\\ \\ \frac{12x - 7}{15x} + \frac{3x - 2}{15x} = \frac{12x - 7 + 3x - 2}{15x} = \frac{15x - 9}{15x} = \frac{3(5x - 3)}{15x} = \frac{5x - 3}{5x} \\ \frac{ax + ay}{x {y}^{2} } \times \frac{ {x}^{2}y }{3x + 3y} = \frac{a(x + y) \times x {}^{2} y}{x {y}^{2} \times 3(x + y)} = \frac{ax}{3y} " align="absmiddle" class="latex-formula">